Reading Habits of Medical Undergraduates in an Academic Library - Angammana, A.M.S.; Ranasinghe, S. (University of Kelaniya, 2017)
Attached

University libraries as academic libraries play a major role in creating academic excellence as well as producing all round personalities. Though university libraries pay special attention in providing subject textbooks to its users, the collection should consists of other categories of resources too. In order to fulfill the needs of the users, librarians need to identify the users reading patterns and behavior. The present study aimed at investigating the use of library books by medical undergraduates. As specific objectives it was intended to find out whether medical students read extra books and whether pattern of reading differ according to study year. Methodology involved is a case study. The population was all undergraduates enrolled in the faculty of medical sciences, University of Sri Jayewardenepura from freshmen to final inthe year 2016. Total population was 1201 and total population was considered as the sample. Quantitative data was collected using the book loan statistics of circulation module of Library management system “KOHA” during the year 2016. Daily statistics of books checked out during January 2016 to December 2016 were analyzed. Subjects were coded using Dewey Decimal classification system.According to demographic data, sample consisted of 21% of males and 79% of females. Number of students who have borrowed books during the year were 610, that is 51% of the sample. Among them 12% were first years while 20%, 26%, 21%, 21% were second, third, fourth and final years respectively. 98% of the first year students have borrowed only textbooks. But this amount has decreased to 76% among final years. Percentages of textbooks borrowed by second, third and fourth years were 92%, 80%, 86% respectively. When considering other categories 17% of final years have borrowed fictions (English, Sinhala and translations) while only 1% of first years have borrowed fictions. This number varied through the study year as 7%, 18%, 10% in second, third and fourth years respectively. Findings revealed that majority of medical students read only textbooks and usage varies among the year of study. The lowest usage was observed from first year students, while third year students had the highest usage. Again in final year there is a decrease in usage. They tend to read other categories of books from third year onwards and most famous category was fictions. Also they have borrowed IT related and General knowledge books.Since this study shows a medium usage of library books, measures should be taken to increase the utilization of books especially by first years and final years. Also authorities should pay attention in fulfilling extra reading needs of medical undergraduates when developing the collection in order to assure effective library usage.
Keywords: University Libraries, Medical undergraduates, Reading behavior, user survey, Book circulation